Sequence Diagram Sebagai Perkakas Perancangan Antarmuka Pemakai - Nofriyadi Nurdam (Ultimatics : Jurnal Teknik Informatika, 2014)
User interface is very important part of an information system. Design requires a serious effort, especially in understanding the user requirements. User interface should support users in completing their tasks. This is becoming the user requirements to be fulfilled by information systems. In reviewing the user requirements a designer can use tools. Tool discussed in this paper is the Sequence Diagram. Index Terms— Information system, design, sequence diagram, tools, user interface, user requirements.